Reformulation and recontextualization in popularization discourse - Maurizio Gotti (Ibérica, 2014)
The paper takes into consideration the evolution of the concept of popularization and of its main techniques of realization in the last few decades. At first, the use of definitions in popularization discourse is investigated and compared to the practices followed in argumentative and pedagogical texts. Special attention is then devoted to the strategies of reformulation and of recontextualization that are often adopted in this process, and exemplifications are provided to highlight the main functions fulfilled by the use of these rhetorical tools. The social importance of popularization is subsequently highlighted together with a discussion of the possible manipulative risks that may be encountered, particularly for argumentative or promotional purposes. The analysis carried out shows the great complexity of the popularization system, which implies therefore the adoption of an integrated approach in order to clearly identify and carefully describe the various aspects involved in this process.